FROM PRIVACY TO OBLIVION: THE RIGHT TO BE FORGOTTEN IN INDONESIA'S SOCIAL MEDIA PLATFORMS - Syari, Shinta Kumala; Simarmata, Sahat Parlindungan; Widyanti, Khairina; Putrijaya, Stefani Nuranugrah (Universitas Dharmawangsa, 2025)
The growing permanence of personal information on social media platforms has created an urgent demand for enhanced legal safeguards for digital identities, especially through mechanisms that allow individuals to request the removal of their data. This is acknowledged in Law No. 27/2022 on Personal Data Protection, its practical implementation within the context of social media still faces significant legal challenges. This article examines how the right to be forgotten is interpreted and operationalized within the social media ecosystem in Indonesia, focusing on platform responsibility and the limitations of user control over their personal data. Through doctrinal legal analysis and socio-legal document review, this article explores the normative scope and real-world application of the right to be forgotten, comparing it with the more established legal guidelines in the European Union. The findings indicate that while there is recognition of the principle of digital erasure, users often find themselves trapped in opaque policies and procedural uncertainties. This article proposes policy recommendations to strengthen user rights, enhance regulatory clarity, and harmonize cross-border enforcement in the digital age.